Pengelolaan Kelas dan Hubungannya dengan Prestasi Belajar Siswa Kelas III Sekolah Dasar - Nomba Nur (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2001)
Classroom Management and Its Relations to the Learning Achievement of the Third Graders of Elementary School. This classroom action research was aimed to find out information whether the learning achievement on social studies was different before and after treatment. The study was carried out in SDN 3 Mattoangin Makassar, South Sulawesi, and involved pupils and teacher of the 3rd grade. The result of the statistical analysis using t-tes showed that the t-value (2.96) was greater than the t-critical value at the level of significance 0.05 with degree of freedom 25 (2.06). It was concluded that there was a significant difference of learning achievement before and after the classroom action research.